2019
DOI: 10.1007/s10734-019-00432-1
|View full text |Cite
|
Sign up to set email alerts
|

Shadows over accreditation in higher education: some quantitative evidence

Abstract: Shadows over accreditation in higher education: some quantitative evidenceAccreditation systems in Higher Education are widespread both in the US and in Europe. However, numerous reservations have appeared in the literature about whether these systems can comprehend and represent the quality of university courses. This study sets out to contribute to this debate by discussing whether the results of the recent university teaching accreditation system in Italy are influenced by the characteristics of degree prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 62 publications
0
10
0
5
Order By: Relevance
“…Ella crea un proceso de autoaprendizaje continuo donde cada uno de los actores gestiona por sí mismo los estándares propuestos hacia la calidad. Además, históricamente ha puesto énfasis en la relación de los procesos de enseñanza aprendizaje, las características de las carreras y la forma en que las personas estudiantes transitan hacia el logro de los saberes disciplinares del programa educativo (Andreani et al, 2020).…”
Section: La Acreditación Y Reacreditación Como Medios Para El Mejoramiento Continuounclassified
“…Ella crea un proceso de autoaprendizaje continuo donde cada uno de los actores gestiona por sí mismo los estándares propuestos hacia la calidad. Además, históricamente ha puesto énfasis en la relación de los procesos de enseñanza aprendizaje, las características de las carreras y la forma en que las personas estudiantes transitan hacia el logro de los saberes disciplinares del programa educativo (Andreani et al, 2020).…”
Section: La Acreditación Y Reacreditación Como Medios Para El Mejoramiento Continuounclassified
“…Other research has compared the accreditation of programs across different disciplines. Recent studies (Andreani et al, 2020;Corengia, 2015;Sin et al, 2017;Stura et al, 2019) have found relevant relationships between the accreditation performance and certain academic disciplines in some programs in Argentina, Italy, and Portugal. The results point out critical differences among disciplines, confirming some of the hypothesized relationships.…”
Section: Approaching the Study Of Academic Disciplines In Accreditationmentioning
confidence: 99%
“…In all these studies, academic disciplines play a strong role in how accreditation impacts specific programs, but it is not the only factor. Other variables, such as geographical location, sector (private or public), and student intake, may also affect the performance of programs in accreditation processes (Andreani et al, 2020).…”
Section: Approaching the Study Of Academic Disciplines In Accreditationmentioning
confidence: 99%
See 2 more Smart Citations